Species Diversity of Helminth Eggs in Soils of Selected Public and Private Primary Schools in Kaltungo, Gombe State - Musa, Ahmad Magaji; Rabiu, Ibrahim; Abubakar, Binta; Umar, Abdulhakim Baraya; Patrick, Detheh Bello; Danjuma, Habiba Joshua; Johnny, Jennifer; Eli, Edith Ishaku; Muhammad, Shamsiyya Umar; Abdullahi, Amina Beni; Simeon, Daniel Olarewaju (Faculty of Natural and Applied Sciences Journal of Basic and Environmental Research, 2025)
Globally, billions of people may be at risk of contracting soil-transmitted helminths (STHs), including whipworm (Trichuris trichiura), roundworm (Ascaris lumbricoides), and hookworms (Ancylostoma duodenale and Necator americanus). This research focused on assessing the variety of helminth eggs found in the soil of chosen public and private primary schools in Kaltungo, Gombe State. A cross-sectional study was conducted, with a total of 280 soil samples were gathered in two phases, March to April 2020 and August to September 2020 repectively. Samples were taken from three locations at each school: near latrines, on playgrounds, and behind classrooms in the schools. To isolate the helminth eggs, floatation and sedimentation methods were utilized. This study identified seven species of helminth eggs: Ancylostoma duodenale (285, 26. 71%), Ascaris lumbricoides (260, 24. 37%), Taenia spp (216, 20. 24%), Toxocara spp. (91, 8. 53%), Strongyloides stercoralis (90, 8. 43%), Fasciola spp (63, 5. 90%), Schistosoma haematobium (32, 3. 00%) and Trichuris trichiura (30, 2. 81%). There were statistically significant differences in species diversity noticed behind classrooms, near latrines, and at playgrounds, with p-values of (0. 0003), (0. 001) and (0. 000) respectively. The level of species diversity in the playgrounds, around latrines and behind classrooms in the selected public and private schools might be deemed moderate. Furthermore, it is essential to implement actions that enhance environmental conditions and promote hygiene through a thorough community-based health education initiative, along with regular de-worming for pets and students.